New Topology of a Hybrid, Three-Phase, Four-Wire Shunt Active Power Filter - Freitas, Stefani; Oliveira, Luis Carlos; Oliveira, Priscila; Exposto, Bruno; Pinto, José Gabriel; Afonso, Joao L. (MDPI, 2023)
With a view to reducing harmonic content in electrical power systems, and, consequently, improving power quality level, filters and other harmonic compensation devices are widely used. In the category of filters, they can be distinguished into two classes that are related to the operating mode, active or passive, both widely known and applied in electrical power grids and in the most diverse industry sectors. In this sense, taking into account the use of compensating devices in four-wire electrical systems feeding single-phase, non-linear loads, this paper presents a new hybrid arrangement of harmonic compensation that incorporates both active and passive filtering, which performs all functions concerning the harmonic compensation of a four-leg shunt active power filter. In this hybrid arrangement, the harmonic filtering of positive and negative sequence components is performed by a three-leg shunt active power filter, while the filtering of zero-sequence harmonics is attributed to the electromagnetic zero-sequence suppressor. The results, which confirm the effectiveness of the proposed hybrid arrangement, are proven through simulations and experimental tests in different operating scenarios, revealing a substantial improvement in the system’s power factor, as well as a reduction in harmonic distortions.
Keywords: electromagnetic suppressor; harmonics; power factor; shunt active power filter